2022
DOI: 10.1186/s12904-022-00982-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural conceptualization of a good end of life with dementia: a qualitative study

Abstract: Background Research on the nature of a “good death” has mostly focused on dying with cancer and other life-limiting diseases, but less so on dementia. Conceptualizing common cross-cultural themes regarding a good end of life in dementia will enable developing international care models. Methods We combined published qualitative studies about end of life with dementia, focus group and individual interviews with the researchers, and video-conferencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…22,51 Although the EOLD-CAD items all assess aspects of quality of dying, the instrument does not cover the full concept of quality of dying, which may include aspects that are more difficult to assess such as retaining identity or dignity. 52 Nonetheless, other such measures do not perform better or properties are unknown. The EOLD-SWC and EOLD-CAD scales have been widely used after an early comparison of psychometric properties, 22 which facilitates comparison between countries.…”
Section: Discussionmentioning
confidence: 99%
“…22,51 Although the EOLD-CAD items all assess aspects of quality of dying, the instrument does not cover the full concept of quality of dying, which may include aspects that are more difficult to assess such as retaining identity or dignity. 52 Nonetheless, other such measures do not perform better or properties are unknown. The EOLD-SWC and EOLD-CAD scales have been widely used after an early comparison of psychometric properties, 22 which facilitates comparison between countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be immoral to leave this solely in the hands of a document based on precedent autonomy which is a very limited format for people with dementia due to their reduced self‐determination. A cross‐cultural study on the conceptualization of a good end of life with dementia found that even in Western countries patients benefit from, and value, relationships more than full autonomy 19 …”
Section: Commentarymentioning
confidence: 99%
“…A cross-cultural study on the conceptualization of a good end of life with dementia found that even in Western countries patients benefit from, and value, relationships more than full autonomy. 19 We are aware that our approach of involving health care providers and family in assessing the desirability of end-of-life interventions may be viewed as paternalistic by advocates of individual autonomy and self-determination. In our view, however, issues such as ceasing assisted feeding are too complex to consider through the narrow lens of autonomy that is statically defined in a directive.…”
Section: Introductionmentioning
confidence: 99%
“…However, qualitative studies from eight countries show that relations are central to a good end of life with dementia. 13 Relations can be complex in dementia. Dementia can have a wide range of potentially detrimental social consequences such as isolation, exclusion, and social distancing of both the person and their close family members.…”
Section: Procedural Requirementsmentioning
confidence: 99%
“…These studies concerning the role of family in euthanasia did not have people with dementia as their main target group. However, qualitative studies from eight countries show that relations are central to a good end of life with dementia 13 . Relations can be complex in dementia.…”
Section: Introductionmentioning
confidence: 99%